Brain age in bipolar disorders: Effects of lithium treatment. (December 2019) - Van Gestel, Holly; Franke, Katja; Petite, Joanne; Slaney, Claire; Garnham, Julie; Helmick, Carl; Johnson, Kyle; Uher, Rudolf; Alda, Martin; Hajek, Tomas
Objective: Bipolar disorders increase the risk of dementia and show biological and brain alterations, which resemble accelerated aging. Lithium may counter some of these processes and lower the risk of dementia. However, until now no study has specifically investigated the effects of Li on brain age. Methods: We acquired structural magnetic resonance imaging scans from 84 participants with bipolar disorders (41 with and 43 without Li treatment) and 45 controls. We used a machine learning model trained on an independent sample of 504 controls to estimate the individual brain ages of study participants, and calculated BrainAGE by subtracting chronological from the estimated brain age. Results: BrainAGE was significantly greater in non-Li relative to Li or control participants, F (2, 125) = 10.22, p  < 0.001, with no differences between the Li treated and control groups. The estimated brain age was significantly higher than the chronological age in the non-Li (4.28 ± 6.33 years, matched t (42) = 4.43, p  < 0.001), but not the Li-treated group (0.48 ± 7.60 years, not significant). Even Li-treated participants with partial prophylactic treatment response showed lower BrainAGE than the non-Li group, F (1, 64) = 4.80, p  = 0.03. Conclusions: Bipolar disorders were associated with greater, whereas Li treatment with lower discrepancy between brain and chronological age. These findings support the neuroprotective effects of Li, which were sufficiently pronounced to affect a complex, multivariate measure of brain structure. The association between Li treatment and BrainAGE was independent of long-term thymoprophylactic response and thus may generalize beyond bipolar disorders, to neurodegenerative disorders.